ERGONOMICS AND POSTURE: RELEVANT ASPECTS IN CONSTRUCTION (Fiep Bulletin - online, 2011)
Ergonomics is the science of designing user interaction with equipment aiming to modify working systems by fitting their existing activities to the limitations, abilities, and characteristics of workers owing to their safe, comfortable, and efficient performance. As literature review, this research seeks to clarify the importance of ergonomics aspects, taking into account adequate posture of construction workers, based on the basics of classic ergonomics work and scientific articles from the database of Sielo, Lilacs, and PPEPS at the Universidade Federal de Santa Catarina. This work is divided in two parts: in the first concepts of ergonomics, in the second one, ergonomics applicability in construction. Results demonstrate concern and urgency on ergonomics preventive measurements in construction in view of the high incidence of construction worker's complain comprising one of the greatest ergonomics challenge facing the diversity of factors and required demands in this area.
Keywords: Ergonomics - Posture - construction